An improved and rapid 5A molecular sieve method for gas chromatography isotope ratio mass spectrometry of n-alkanes An improved and rapid 5A molecular sieve method for gas chromatography isotope ratio mass spectrometry of n-alkanes (C8–C30+) - Grice, Kliti; de Mesmay, Romain; Glucina, Andrew; Wang, Sue Xuan (Elsevier Science, 2008)
The accurate analysis of stable carbon isotope ratios of individual n-alkanes in petroleum by gas chromatography isotope ratio mass spectrometry (GC-irMS) requires that the n-alkanes be separated from branched/cyclic hydrocarbons. Conventional separation methods include urea adduction or separation using different types of molecular sieves (5A, ZSM5). Although the molecular sieves procedures are well established, they generally require the use of hydrofluoric (HF) acid, a potentially hazardous material, to digest and release compounds trapped within the sieve. In this study, a simplified 5A method that avoids the use of HF acid has been developed to isolate n-alkanes ranging from n-C8 to at least n-C30 from a saturated petroleum hydrocarbon fraction. 12% cyclohexane in n-pentane was found to be a sufficient solvent in extracting most of the n-alkanes (>90%) in the n-C8 to n-C30 range from the sieve. The new 5A sieve procedure is a rapid and safer method for extracting n-alkanes from petroleum to yield fractions amenable for routine GC-irMS.